2003
DOI: 10.1002/ar.a.10133
|View full text |Cite
|
Sign up to set email alerts
|

Blood cell progenitors: Insights into the properties of stem cells

Abstract: Hematopoiesis is a dynamic process in which eight lineages of mature blood cells are derived from a common stem cell. Great progress has been made in identifying the functionally disparate progenitors that emerge from the stem cell and in elucidating the molecules required for their growth and survival. Further work will be required to understand the molecular mechanisms that regulate commitment of stem and progenitor cells to each stage of progenitor cell development and ultimately into the mature blood cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…However, in the last years a number of publications have provided evidences for a greater plasticity of stem cell commitment and differentiation (Young and Black, 2004). For example, bone marrow cells, including isolated populations of hematopoietic stem cells have been reported to differentiate into muscle, neurons, liver, vascular, lung, intestine and kidney tissue (Yoder, 2004). In addition, it has been shown that stem cells obtained from adult bone marrow not only were able to differentiate into cardiomyocytes but also contributed to restore cardiac function when either injected directly into the injured adult heart (Tomita et al, 1999) or exposed to myocardium via circulation (Orlic et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last years a number of publications have provided evidences for a greater plasticity of stem cell commitment and differentiation (Young and Black, 2004). For example, bone marrow cells, including isolated populations of hematopoietic stem cells have been reported to differentiate into muscle, neurons, liver, vascular, lung, intestine and kidney tissue (Yoder, 2004). In addition, it has been shown that stem cells obtained from adult bone marrow not only were able to differentiate into cardiomyocytes but also contributed to restore cardiac function when either injected directly into the injured adult heart (Tomita et al, 1999) or exposed to myocardium via circulation (Orlic et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The ontogeny of the hematopoietic system has been investigated in multiple model systems from Drosophila to man, but study of the mouse has provided many fundamental insights due to the ready availability of functional transplantation and colony‐forming assays for hematopoietic stem cells (HSCs) and progenitor cells, respectively . Another advantage of the murine system is the availability of flow cytometry‐based methods to quantitate hematopoietic stem and progenitor cell populations, and to isolate them for study.…”
mentioning
confidence: 99%
“…Furthermore it has been shown that BM‐derived cells do not stably incorporate into newly formed vessels and only play an auxiliary role in neovascularization . True vasculogenic ability has only been demonstrated for a single cell‐type, designated the endothelial colony forming cell (ECFC) , which cannot be obtained from BM. While the auxiliary angiogenic effects of BM‐MNCs have been demonstrated very consistently in animal models, it is likely that they only occur with BM isolates from comparatively young subjects without comorbidities .…”
Section: Cell Therapy For Clti—the Present State Of Affairsmentioning
confidence: 99%